CISG - what risks does it involve to seller and how does he secure against them? - a practical guide - Christiansen, Lisbeth (Department of Commercial Law, 2014)
The purpose of this dissertation is to identify what risks the CISG involves for seller and to describe how he can allocate, reduce or eliminate these risks. For this purpose I will make use of cases judgments as well as arbitration awards as they will hopefully give a better picture of what risks seller is exposed to in "the real life" than the wording of the CISG itself does. The internet provides numerous cases involving the Convention. I will only concentrate on the leading cases.